Humanism and ideology. Issue 6 (18th September 2016) - Sinfield, Alan
ABSTRACT: Combining autobiographical and theoretical reflections, this essay looks back impressionistically on the last 100 years of British/US LGBTQ history. The discussion draws on exemplary texts from a range of media; these texts include Brokeback Mountain, Auden's poetry, Rattigan's drama, queer oral history, and gay journalism.